Oxygen Plasma Treatment of Platinized Ultramicroelectrodes Increases Sensitivity for Hydrogen Peroxide Detection on Mitochondria. Issue 3 (24th January 2013) - Ben‐Amor, Salem; Devin, Anne; Rigoulet, Michel; Sojic, Neso; Arbault, Stéphane
Abstract Hydrogen peroxide is a major bio‐active molecule produced by mitochondria during aerobic metabolism. In order to monitor that production, platinized ultramicroelectrodes with high surface‐area were used. Their sensitivity was significantly improved following an oxygen plasma treatment. Cyclic voltammetry and chronoamperometry analyses of ferricyanide reduction and hydrogen peroxide oxidation showed that ultramicroelectrodes' capacitive current was decreased 3‐fold, while faradaic currents remained constant. Then, plasma‐treated ultramicroelectrodes allowed the chronoamperometric detection of 100 nM H2O2 injections. This eventually enabled monitoring the mitochondria release of H2O2 following injection of substrates and a respiratory inhibitor; a flux of few hundreds picomoles H2O2/mg protein/min was detected.